Two new species of Rhinophis Hemprich (Serpentes: Uropeltidae) from Sri Lanka - Gower, David J.; Maduwage, Kalana (Zootaxa, 2011)
Two new species of uropeltid (shieldtail) snake are described from Sri Lanka; Rhinophis lineatus sp. nov. from Harasbedda, near Ragala, and Rhinophis zigzag sp. nov. from Bibilegama, near Passara. The new species are distinguished from congeners in morphometric and meristic external characters, and in having very distinctive colour patterns. Scale-row reduction data are presented for the two new species; this is a new development for uropeltid systematics, and its potential utility is highlighted. The nature of the overlap between the two anal scales is also highlighted as a potentially useful character. The two new species were included in previous phylogenetic analyses of allozyme and albumin immunological data, but their phylogenetic relationships are not yet well resolved.